The Effects of PAD, DAU, and Employee Expenses on Capital Expenditures with Population Density as a Moderating Variable - Jati, Kuat Waluyo; Subowo, Subowo; Ilmiyana, Wina; Sari, Maylia Pramono (Jurnal Dinamika Akuntansi, 2019)
The aims of this study are to analyze the effect of PAD, DAU, and employee expenses on capital expenditure with population density as a moderating variable. The main theories are stewardship and resource dependency theory. The population is 35 districts/cities in Central Java in 2013-2017. There are 175 units that chosen by saturated sampling method. There are 14 of outlier data. Thus, there are 161 unit of analysis. The analytical tools used are descriptive statistic, inferential analysis, and MRA. The results showed that PAD have positive and significant effect on the capital expenditure, DAU does not have significant effect on the capital expenditure, employee expenditure does not have negative and significant effect on the capital expenditure. Population density can moderate the effect of PAD on the capital expenditure. However, population density cannot moderate the effect of DAU and employee expenses on the capital expenditure. The conclusions are PAD has a significant positive effect on the capital expenditure and employee expenses have a significant negative effect on the capital expenditure. It can be a reason that regional governments must increase PAD and reduce employe expenses for capital expenditure.